NEUROCHIPS AND THEIR PROPERTIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides information about the history of the development of neurochips, the Neuralink project, the principles of operation, practical application and their impact on the future of mankind, namely the benefits and dangers.